A non-functional 5′ ALK fusion validated at the RNA level as a classical EML4-ALK that responds well to the novel ALK inhibitor ensartinib: A case report - Yang, Hong; Li, Haojing; Fang, Yu; Li, Zhijun; Zhu, Jianhua; Liu, Huan; Lu, Chao; Zhang, Xiaoyan; Ma, Tonghui; Zhang, Cuiying (Frontiers in Medicine, 2022)
Background: Currently, many targeted drugs are approved for the treatment of ALK fusion non-small cell lung cancer. However, it was previously assumed that patients with 5' nononcogenic kinase (5' NOK) fusion detected by DNA next generation sequencing (NGS) would not benefit from ALK inhibitors because of the lack of an intact kinase domain. Case Description: A novel 5' NOK fusion form, ALK-CYP27C1 (A19:C5), was detected by DNA NGS in surgical tissue specimens of a recurrent lung adenosquamous carcinoma patient. The patient achieved 29 months of progression-free survival with ensartinib treatment. The results of RNA NGS from the same operative tissue identified EML4-ALK (E13:A20) fusion variant type I. Conclusions: This is the first case to provide real-world evidence of the effective treatment of patients with the 5' NOK fusion form at the DNA level but functional EML4-ALK at the RNA level, illustrating the need for RNA testing in such 5' NOK patients.